Diagnosis of cervical lesion by colposcopy, VIA, pap smear tests, and their correlation with histopathology in a tertiary level laboratory in Chattogram, Bangladesh - Siddiqui, Syeda Rumman Aktar; Islam, M. Ariful; Rahman, M. Zillur (International Journal of Research in Medical Sciences, 2023)
Background: Cervical carcinoma is one of the most common causes of mortality among women. This mortality rate can be reduced by early detection of cervical neoplasm by different screening tests. The main objective of this study was to diagnose cervical diseases by colposcopy, by pap smears for cytological examination as well as correlate these findings as screening tests with histopathological diagnosis. Methods: In this cross-sectional observational study, total 143 cases were included. History was taken and clinical examination was done. Colposcopy and VIA test was done, pap smear sample was collected and reporting was made. Cytological findings were correlated with histopathology. Results: Mean age of the study cases was 41.2±11.5 years. VIA test was positive in 98 study cases (68.5%). On colposcopy, most of the cases show neoplastic proliferation (80 cases, 55.9%). Among them, most cases were diagnosed as cervical intraepithelial neoplasia-I (CIN-I). Sixty-three (63) cases (44.1%) were non-neoplastic. Most of the biopsies was diagnosed histopathologically as cervical intraepithelial neoplasia-I (CIN-I) (20 cases, 14.0%). Association of colposcopy findings with histopathological diagnosis was done which was significant. Sensitivity of diagnosis of cervical malignancy by colposcopy was 33.33% and specificity was 98.57%. Conclusions: The study provides good cyto-histopathology correlation in detecting different cervical lesions and malignancy with colposcopy. Although colposcopy sensitivity was low but it can be increased by adequate training and avoiding technical errors. Bethesda system is strongly recommended for adequacy of sampling to minimize inconsistency. Early and regular screening should be advised for reduction of mortality rates from cervical carcinoma.